Vapour Phase Ethylation of Benzene Over ZSM-5 Synthesized in Fluoride Medium - Hariharan, S.; Palanichamy, M.; Murugesan, V. (Asian Journal of Chemistry, 2012)
ZSM-5 zeolite (Si/Al ratio 50, 75 and 100) was hydrothermally synthesized in fluoride medium. Their crystal size and crystallinity were high. SEM images of synthesized material showed large elongated prismatic crystals. Their catalytic activity was examined for vapour phase ethylation of benzene between 200 and 400 ºC. The ethylbenzene conversion was high at 300 ºC compared with other temperatures. The selectivity of ethylbenzene was high at low ethanol content in the feed, but decreased with an increase in ethanol content. Among the diethyl benzene isomers the selectivity of p-diethyl benzene was higher than others. High selectivity of p-diethyl benzene was due to large crystal size and high crystallinity. Hence synthesis of ZSM-5 in fluoride medium could catalyze para selective ethylation of ethylbenzene. The same catalyst could also be applied to other selective alkylations.